Management skills to promote participation families in basic schools - Barrientos Piñeiro, Claudio (2016)
This article provides knowledge about the state of affairs on policies and dynamicssurrounding the performance skills of school principals regarding the promotionof participation. Using a qualitative approach and methodology Case Study resultsshowed traditionalist practices and promotion strategies, passive involvement offamilies, with minimum levels of participation were obtained. The managementperformance is presented restrictive weak presence of attitudes toward empathy,trust and do dialogic, thus weakening the commitment of parents to participatein schools. The importance it attaches to social skills, personal qualities and valuesthat should mobilize managers to adequately promote parent and communityparticipation is emphasized.